2016
DOI: 10.1177/0020764016653980
|View full text |Cite
|
Sign up to set email alerts
|

Symptom endorsement in men versus women with a diagnosis of depression: A differential item functioning approach

Abstract: . (2016). Symptom endorsement in men versus women with a diagnosis of depression: A differential item functioning approach. International Journal of Social Psychiatry, 62 (6), 549-559.Symptom endorsement in men versus women with a diagnosis of depression: A differential item functioning approach Abstract Background: There is some evidence that, in contrast to depressed women, depressed men tend to report alternative symptoms that are not listed as standard diagnostic criteria. This may possibly lead to an unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 47 publications
2
17
0
Order By: Relevance
“…Features of this subtype include: a sudden and periodically lowered stress tolerance in otherwise stress resistant men; impulsive‐aggressive or psychopathic personality disorder in otherwise nonpsychopathic persons; and suddenly occurring endorphin‐ or serotonin‐related behavior, such as alcohol and other drug abuse or workaholism in otherwise nonabusive men . Men appear to mask depression by atypical symptoms such as anger, hostile‐aggressive‐abusive behavior, or irritability, which may lead to depression being underdiagnosed and undertreated in men . Mental health problems were often comorbid physical conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Features of this subtype include: a sudden and periodically lowered stress tolerance in otherwise stress resistant men; impulsive‐aggressive or psychopathic personality disorder in otherwise nonpsychopathic persons; and suddenly occurring endorphin‐ or serotonin‐related behavior, such as alcohol and other drug abuse or workaholism in otherwise nonabusive men . Men appear to mask depression by atypical symptoms such as anger, hostile‐aggressive‐abusive behavior, or irritability, which may lead to depression being underdiagnosed and undertreated in men . Mental health problems were often comorbid physical conditions.…”
Section: Discussionmentioning
confidence: 99%
“…40 Men appear to mask depression by atypical symptoms such as anger, hostile-aggressive-abusive behavior, or irritability, 40 which may lead to depression being underdiagnosed and undertreated in men. 42 Mental health problems were often comorbid physical conditions. Research has indicated significant associations between somatic and psychological symptoms and depression in farmers, 43 and specific physical illnesses (eg, pain and arthritis) and functional disability with suicidal behaviors in older adults.…”
Section: Discussionmentioning
confidence: 99%
“…This over‐representation of women can be due to several factors, including that women are more likely to receive ART than men [50,51]. Women tend to present with affective symptoms while men tend to self‐medicate depressive symptoms with substances [52], which is not assessed using the PHQ‐9. No clinic characteristics were consistently associated with gaps in receiving care.…”
Section: Discussionmentioning
confidence: 99%
“…2 It may also be that some of the symptoms of depression in men -such as alcohol misuse or antisocial behaviour -are not diagnosed as such, 3 leading to the suggestion that a different set of diagnostic criteria should be used for men. 4 The Royal College of Psychiatrists suggests that, in fact, men suffer from depression to the same extent as women. There are several specific mental health issues where the burden on men is very clear.…”
Section: The Scale Of the Problemmentioning
confidence: 99%